A Literature Review of Health and Mental Well-being Indicators and Its Assessment in Sub-Saharan Africa (2014-2022) - Jumoke Iyabode Oladele; Tharina Guse; Henry O Owolabi (Gonabad University of Medical Sciences, 2024)
Background: Multiple factors shape health and mental well-being (MWB). These factors are considered indicators for a holistic assessment of the well-being construct. Analyzing existing literature on indicators related to health and MWB is necessary to support a comprehensive evaluation in the sub-Saharan African context to assess and improve the population's health and MWB. Methods: This study is a literature review conducted by adapting the POWER framework while leveraging the Web of Science (WoS) database, complemented with random Google-led searches. Leveraging the POWER framework, this paper reviewed related literature on mental health and well-being (HWB) to provide a framework for action.  Results: Going through the planning, writing, and reflection phases, of the POWER framework, the WoS database search produced 22 pieces of literature published in South Africa from 2014 to 2022 and 5 pieces of literature published in Nigeria from 2019 to 2022 with 26 manuscripts across higher institutions in South Africa and eight manuscripts with various organizations. The study revealed abilities to realize potential, cope with the normal stresses of life, work productively and fruitfully, and meaningful community engagement as some of the crucial mental health indicators. The reviewed literature revealed that MWB as a multi-phased construct is fast gaining attention in sub-Saharan African contexts. Conclusion: This study concluded that mental HWB assessment has multiple indicators being largely deployed linearly using Western-developed or validated assessment instruments. Therefore, an adaptive health and MWB assessment with a more accurate assessment capacity should be developed as a transdicsiplinary illness prevention intervention.